Combined 18F-FDG-PET/CT imaging of the head and neck - Schäfers, K. P.; Raupach, R.; Beyer, T. (Nuklearmedizin - NuclearMedicine, 2006)
PET/CT imaging is particularly promising for head/neck malignancies, but dental implants lead to biased CT attenuation and PET activity values following CT-based attenuation correction (CT-AC). Objective: Here, we implement a metal artifact correction procedure (MAR) as part of the CT-AC for PET/CT imaging. Results: Phantom studies indicate a maximum quantitative bias in CT and PET of 1000 HU and 30 %, which is reduced to 230 HU and 6 %, respectively following MAR. These results were verified in selected patients. Conclusion: Artifacts and biases from dental implants can be reduced in PET/CT imaging by applying a simple MAR as part of the CT-AC.
Keywords: Head and neck; metal artifacts; PET/CT imaging